INTERSYSTEMISCHER RECHTSVERGLEICH UND INTERLINGUALE RECHTSÜBERSETZUNG NORWEGEN UND DEUTSCHLAND - SIMONNÆS, Ingrid (Comparative Legilinguistics, 2019)
This paper presents theoretical aspects of the intersystemic translation of legislative texts from Norwegian into German for informative purposes. When comparing legal systems, one differentiates between international, national and supranational legal systems. Since each legal system has its own conceptual system, the prevailing challenge in legal translation (studies) is how to reconcile different conceptual systems and their denominations in two different legal languages. Therefore, it is often argued that the ideal profile for a legal translator should consist of a combination of skills of both lawyers and linguists. In this vein, a case study on recent changes in Norwegian and German family law concerning motherhood/fatherhood is used to illustrate an interdisciplinary approach to translating central concepts from Norwegian into German.